Cost efficient low-emission housing: implications for household cash-flows in Melbourne. (1st January 2014) - Moore, Trivess; Morrissey, John; Horne, Ralph
A number of international jurisdictions have articulated a longer term goal of zero emission housing standards. However, in Australia, housing energy efficiency remains a contested policy area. In part, this is due to a lack of clear cost-benefit information on low emission housing standards, including impacts at the household level. This research investigated the lifetime economics of low emission housing options for typical housing in Melbourne, Australia. The analysis found that for a zero emission house, there was an additional capital cost of 25, 637. This translated into extra yearly mortgage repayments of 2, 117 at an interest rate of 7.89% across 25 years. However, energy efficiency cost savings of 1, 547 a year were calculated, leaving a gap of 570/year in additional mortgage repayments. As a result, policy makers in Australia should focus on reducing upfront costs and developing innovative financial frameworks in order to make low emission housing achievable.